(untitled) (Academia Science Repository, 2023)
The article talks about the student’s declarative knowledge and investigates how Declarative knowledge describes things, events and processes, as well as their relationship to each other. According to the activity theory of education, the ultimate goal of education is to form a method of action, and it is assumed that the method of action is implemented through skills in practical activities.